Impact of nitrogen-fixation bacteria on nitrogen-fixation efficiency of Bambara groundnut [Vigna subterranea (L) Verdc] genotypes - Bitire, Tope Daniel; Abberton, Michael; Tella, Esther Oluwabukunola; Edemodu, Alex; Oyatomi, Olaniyi; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2023)
Nitrogen fixation by bacteria is very essential forin sustaining the growth, development, and yield of legumes. Pot experiments were carried out at the International Institute of Tropical Agriculture (IITA) in the , glasshouse between August and December of 2018/2019 cropping season in Ibadan, Nigeria. Field studies were also performed in two different agroecologicaly zones, "Ibadan and Ikenne" between August and December of 2019/2020 cropping season., Tthe studies were set up to determine the potentials of nitrogen fixing bacteria strains inoculation, on nitrogen-fixing potential of ten accessions of Bambara groundnut (BGN) genotypes, namely: TVSu-378, TVSu-506, TVSu-787, TVSu-1606, TVSu-1698, TVSu-1739, TVSu-710, TVSu-365, TVSu-475, and TVSu-305. The strains were inoculated as a broth to seedlings of each BGN genotype accessions in the pot experiment. While sWhile six seeds from each accessions of BGN genotype were coated with each of the following nitrogen fixing bacteria (Bradyrhizobium japonicum strains): FA3, USDA110, IRJ2180A, and RACA6,. nNitrogen fertilizer (urea, 20kg/ha) wasere appliedy as a check to the nitrogen fixing bacteria, to seedlings of BGN genotypes accessions at two weeks after planting in both glasshouse and on the fields. Uninoculated plant serves as control (zero inoculation and zero fertilization). The field experimentss were arranged in Randomized Complete Block Design (RCBD), while the glasshouse experiments were arranged in Complete Randomized Design (CRD) in triplicates. Result obtained revealed that higher nodules number and weight were recorded in TVSu-1739 and TVSu-475 in both locations and seasons, compared to other genotypes, the highest nitrogen fixed were recorded among BGN genotypes accessions TVSu-1739, TVSu-1698, TVSu-787, TVSu-365, TVSu-305, TVSu-710 and TVSu-1606 with a range of (62-67 kg ha -1 );, and were mostly enhanced by RACA6, and USDA110 strains compared to other strains that were used.The study conclude that the nitrogen fixing bacteria enhanced the nitrogen fixing potential of BGN accession compared to the inorganic N fertilizer applied.